2008
DOI: 10.1007/s11469-007-9144-y
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Personality Variables in Drug Abuse in a Spanish University Population

Abstract: This article explores the relationships between certain cognitive and emotional factors (sensation seeking, impulsivity, self-esteem, anxiety sensitivity and loneliness) and regular consumption of alcohol and other drugs by a university population from Almería (South Spain). During 2005 and 2006 students were given a battery of questionnaires related to these personality variables and the substances they had consumed. After filling out the psychometric tests, the participants gave a urine sample which was then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Study Characteristics Five studies investigated the association between global substance use and self-esteem [46,[80][81][82][83]. All the studies were cross-sectional and included between 243 and 506 students, whereas 1 study included 2407 participants [83].…”
Section: Directionality Of the Associationmentioning
confidence: 99%
See 3 more Smart Citations
“…Study Characteristics Five studies investigated the association between global substance use and self-esteem [46,[80][81][82][83]. All the studies were cross-sectional and included between 243 and 506 students, whereas 1 study included 2407 participants [83].…”
Section: Directionality Of the Associationmentioning
confidence: 99%
“…All the studies were cross-sectional and included between 243 and 506 students, whereas 1 study included 2407 participants [83]. Self-esteem was evaluated exclusively by a global self-esteem measure, including three studies with the RSE scale [46,80,81]. Two studies included undergraduate students [82,83].…”
Section: Directionality Of the Associationmentioning
confidence: 99%
See 2 more Smart Citations
“… 7 9) However, the role of psychological disorders specifically in sedative drug use has not been characterized, so this characterization is one of the objectives of the present study. Previous studies have suggested contributions of personality factors in drug abuse; 7 10 11) therefore we evaluated the relationship between alexithymia and sedative drug use.…”
Section: Introductionmentioning
confidence: 99%